Official Dollarization As a Monetary Regime : Its Effectson El Salvador - Swiston, Andrew (IMF Working Papers; Working Paper ;, 2011)
This paper examines El Salvador's transition to official dollarization by comparing aspects of this regime to the fixed exchange rate regime prevailing in the 1990s. Commercial bank interest rates are analyzed under an uncovered interest parity framework, and it is found that dollarization lowered rates by 4 to 5 percent by reducing currency risk. This has generated net annual savings averaging 1\2 percent of GDP for the private sector and u percent of GDP for the public sector (net of the losses from foregone seigniorage). Estimated Taylor rules show a strong positive association between Salvadoran output and U.S. Federal Reserve policy since dollarization, implying that this policy has served to stabilize economic activity more than it did under the peg and more than policy rates in Central American countries with independent monetary policy have done. Dollarization does not appear to have affected the transmission mechanism, as pass-through of monetary policy to commercial interest rates has been similar to pass-through under the peg and in the rest of Central America.